PbrBGAL6 promotes pollen tube growth by influencing apical pectin level in Pyrus bretschneideri - Yusheng Xu; Lan Xu; Mingliang Zhang; Hao Wang; Yuqian Wang; Xueping Zhang; Kaijing Zhang; Yihu Sui; Jingjing Qian; Shuangshuang Jia; Ming Qian; Guangrong Cui (BMC Genomics)
Abstract Background β-galactosidase (BGAL), which is an important cell wall-degrading enzyme, participates in various biological processes, but its effects on pollen tube growth (PTG) remain unclear. Results We identified 12 PbrBGAL genes (named PbrBGAL1–12) in the pear (Pyrus bretschneideri) genome. PbrBGAL members, containing three conserved domains and two enzyme active sites, were grouped into six subclasses. They were distributed in seven chromosomes, with dispersed duplication revealed as the main replication event. PbrBGAL genes contained 1 to 24 exons and 0 to 23 introns, with exon/intron structure mostly conserved within each subclass except for subclass E. Analyses of tissue-specific expression indicated that only PbrBGAL6 was highly expressed specifically in anther and pollen, with decreasing expression levels during PTG. The effective inhibition of PbrBGAL6 expression using antisense oligodeoxynucleotide technology dramatically decreased BGAL enzymatic activity, promoted PTG and increased cytoplasmic leakage and tip widths. Furthermore, suppressing PbrBGAL6 transcription decreased the apical total and methylated pectin contents in pollen tubes by significantly increasing transcription of PbrPME11, PbrPG14, PbrPG20, PbrPG21 and PbrPG24. Conclusions We identified 12 PbrBGAL genes in the pear genome, of which PbrBGAL6 precisely modulates the apical pectin content to mediate pear PTG through its effects on PbrPME11 and PbrPGs expression. This study provides direct evidence of the involvement of BGAL in the regulation of polar PTG.